TADAKHUL AL-LUGOH AL-UMM ‘ALĀ AL LUGOH AL-AJNABIYAH FI AL MUHĀDATSAH LADA AT-TALAMIDZ BI MA’HAD NUR AL-HIDĀYAH TANGERANG - Hasaniyah, Nur; Mahyudin, Erta; Midi, Utin Candra (Annual International Conferences on Language, Literature, and Media, 2022)
This research aims to describe the types of language interference occurred in Nour Al-Hedaya boarding school, to reveal the description of the main factors that occur in the language and the efforts made to overcome the language interference. The research is a qualitative and the methods used to collect the data are observation, interview and documentation. The results of this research are: 1) The types of conversational interference in pupils of Noor Al-Hedaya boarding school are phonemic interference 35, 5%, grammatical interference 57%, pure interference 50%, vocabulary interference 60%, and stereotypical interference 47%; 2) The factors that cause interference in the mother tongue in a foreign language are phonemic and individual interference, grammatical interference, pure interference, stylistic interference; and 3). The efforts to overcome interference are divided into two parts, they are internal effort and external effort. The research summary had an average of over 50% of language intervention of almost all of the types.